Causal associations between sleep traits and brain structure: a bidirectional Mendelian randomization study - Qiao Wang; Shimin Hu; Lei Qi; Xiaopeng Wang; Guangyuan Jin; Di Wu; Yuke Wang; Liankun Ren (Behavioral and Brain Functions, 2023)
Abstract Background Emerging evidence suggests bidirectional causal relationships between sleep disturbance and psychiatric disorders, but the underlying mechanisms remain unclear. Understanding the bidirectional causality between sleep traits and brain imaging-derived phenotypes (IDPs) will help elucidate the mechanisms. Although previous studies have identified a range of structural differences in the brains of individuals with sleep disorders, it is still uncertain whether grey matter (GM) volume alterations precede or rather follow from the development of sleep disorders. Results After Bonferroni correction, the forward MR analysis showed that insomnia complaint remained positively associated with the surface area (SA) of medial orbitofrontal cortex (β, 0.26; 95% CI, 0.15–0.37; P = 5.27 × 10–6). In the inverse MR analysis, higher global cortical SA predisposed individuals less prone to suffering insomnia complaint (OR, 0.89; 95%CI, 0.85–0.94; P = 1.51 × 10–5) and short sleep (≤ 6 h; OR, 0.98; 95%CI, 0.97–0.99; P = 1.51 × 10–5), while higher SA in posterior cingulate cortex resulted in a vulnerability to shorter sleep durations (β, − 0.09; 95%CI, − 0.13 to − 0.05; P = 1.21 × 10–5). Conclusions Sleep habits not only result from but also contribute to alterations in brain structure, which may shed light on the possible mechanisms linking sleep behaviours with neuropsychiatric disorders, and offer new strategies for prevention and intervention in psychiatric disorders and sleep disturbance.